(untitled) (Global Conference on Medical and Health Sciences, 2026)
Diabetes mellitus is one of the most pressing problems of modern medicine and represents a significant risk factor for the development of cardiovascular diseases. According to the World Health Organization, patients with diabetes mellitus have a significantly higher risk of developing cardiovascular diseases, particularly ischemic heart disease, which is one of the leading causes of disability and mortality worldwide.